Cegah Stunting: Indonesia Tumbuh Sehat dan Hebat Desa Jogoyitnan, Kecamatan Wonosobo, Kabupaten Wonosobo - Nugroho, Adhi Wahyu; Puji Hartono, Febrian Rizki; Perwitosari, Warih; Widhianingrum, Wahyu Astri (Yayasan Inspirasi El Burhani, 2024)
Abstract Introduction: Thematic KKN is an academic activity with a clear theme and program. This activity partner aligns research and community service programs with internal and external funds. KKN activities were carried out in Jogoyitnan Village, Wonosobo District, Wonosobo Regency with the theme